2015
DOI: 10.1016/j.canlet.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The differential role of human macrophage in triggering secondary bystander effects after either gamma-ray or carbon beam irradiation

Abstract: The abscopal effect could be an underlying factor in evaluating prognosis of radiotherapy. This study established an in vitro system to examine whether tumor-generated bystander signals could be transmitted by macrophages to further trigger secondary cellular responses after different irradiations, where human lung cancer NCI-H446 cells were irradiated with either γ-rays or carbon ions and co-cultured with human macrophage U937 cells, then these U937 cells were used as a bystander signal transmitter and co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Teresa Pinto et al [20] also found that irradiated macrophages promote cancer cell invasiveness and cancer cell-induced angiogenesis. Besides, the abscopal effect may be a crucial factor in evaluation of the prognosis associated with radiotherapy, and TAMs can release secondary bystander signals and play a key role in the secondary bystander effect of photon irradiation [21]. Targeting TAMs or TAM-associated signaling to enhance the potency of radiotherapy has been similarly demonstrated in several other studies [14, 2224].…”
Section: Tams Lead To a Poor Clinical Prognosis And Promote Progrementioning
confidence: 95%
“…Teresa Pinto et al [20] also found that irradiated macrophages promote cancer cell invasiveness and cancer cell-induced angiogenesis. Besides, the abscopal effect may be a crucial factor in evaluation of the prognosis associated with radiotherapy, and TAMs can release secondary bystander signals and play a key role in the secondary bystander effect of photon irradiation [21]. Targeting TAMs or TAM-associated signaling to enhance the potency of radiotherapy has been similarly demonstrated in several other studies [14, 2224].…”
Section: Tams Lead To a Poor Clinical Prognosis And Promote Progrementioning
confidence: 95%
“…Cytokine engagement of receptors on neighbouring cells can trigger a cytokine cascade that upregulates death receptors on the cell surface, and/or induces cell death; IL-1α, IL-6, IL-8, TGF-β1, TNF-α/β (Burdak-Rothkamm et al 2007; Dong et al 2015; Ivanov and Hei 2014a; Narayanan et al 1999; Shao et al 2007, 2008; Shareef et al 2007). The interconnected network of pro-inflammatory cytokines, ROS and apoptotic ligands contributes to ‘cytokine’- and ‘bystander’-induced cell death.…”
Section: Radiation-induced Immune Mediatorsmentioning
confidence: 99%
“…Senescent–like cell death is more common among cells of epithelial origin (Suzuki et al 2001), compared to haematopoietic cells which predominantly undergo apoptosis due to the relative radiosensitivity of the cell types (Ross 1999). IR of normal human keratinocytes induced ROS-mediated premature senescence by the up-regulation of oxidase genes Lpo, p22-phox, p47-phox and Gp91 (Dong et al 2015). Normal human diploid cells irradiated with X-ray radiation lead to permanent cell growth arrest through the accumulation of p53 and induction of p21 WAFI/CIP1 and p16.…”
Section: Radiation-induced Immune Mediatorsmentioning
confidence: 99%
“…To date, a large variety of signaling molecules have been proved as pivotal bystander modulators including free radicals91011, calcium flux12, interleukins13, cytochrome-c1114, cAMP15, transforming growth factors-β1 (TGF-β1)16, tumor necrosis factor-α (TNF-α)17, nuclear factor kappa B (NF-κB)18 and MAPK1819. In addition, most previous studies of RIBE have focused on these signaling molecules transferring from irradiated cells toward non-irradiated bystander cells.…”
mentioning
confidence: 99%
“…However, extensive in vitro and in vivo studies have demonstrated that in response to irradiation, cancer cells could also evoke bystander responses to normal tissue and cells101320, which may enhance the occurrence of the secondary cancer risk after radiotherapy. On the other hand, it was reported that bystander responses could induce differentiation of primary cells and have a protective role in removing potentially damaged cells in response to low dose irradiation and then decrease radiation cancer risk8.…”
mentioning
confidence: 99%